Phosphane gold(i), silver(i) and copper(i) dithiocarbamates: Synthesis, characterization, anti-cancer and anti-bacterial studies / Nazzatush Shimar Jamaludin - Nazzatush Shimar, Jamaludin (2015)

(untitled)
In this study, three functionalized dithiocarbamate ligands [-S2CN(R)CH2CH2OH] were reacted with phosphanegold(I), silver(I) and copper(I) precursors resulting in their respective dithiocarbamate complexes. The molecular structures of these compounds were elucidated using various spectroscopic methods: NMR (1H, 13C{1H} and 31P{1H}), IR, as well as by X-ray methods: powder X-ray diffraction (PXRD) and single crystal X-ray diffraction (SCXRD). These compounds were also tested for their biological efficacies in order to identify potential candidates as anti-cancer and anti-bacterial agents. The successful synthesis of the complexes was determined by NMR and IR methods whereby the interpretation agrees well with literature. The powder patterns of the compounds are of similar to the single crystal data, when crystal structures obtained showed that the gold compounds had linear coordination geometries while the copper and silver compounds has tetrahedral geometries. Phosphanegold(I) derivatives with isopropyl dithiocarbamate ligand group were found to exhibit excellent anti-proliferative activity against MCF-7R breast cancer cells and anti-bacterial activity against almost a wide spectrum of Gram-positive and Gram-negative pathogens. Nevertheless, the phosphanegold(I) derivatives with the isopropyl-substituted dithiocarbamate were also toxic to non-cancerous human cells. The phosphanesilver(I) and -copper(I) dithiocarbamates for all series of ligands also showed promising anti-proliferative activity against a number of cancer cell lines: liver (HepG2), breast (MCF-7R), ovarian (A2780), colon (HT-29), lung (A549) and thyroid iv (8505C) cancer cells. However, these series were also toxic on non-cancerous human cells with the exception on human embryogenic kidney (HEK293) cells.